Institutional underpinnings of the development of knowledge sub-systems in Central and Eastern Europe - Adam Karbowski (Ekonomista, 2017)
Knowledge sub-system encompassing innovation, research and education is one of the key institutional domains that constitute each national political economy. Over the last fifteen years the knowledge sub-systems have undergone profound transformation to emerge as the main motors of industrial competitiveness, growth and development in a globalized world. This paper thoroughly reviews the large body of literature on knowledge sub-systems in CEE countries. The resulting policy conclusions are so far ambivalent. The most immediate implication would be for the CEE economies to substantially invest in education, training and research in order to stabilize their current comparative advantages against the relocation of production and to attract new investments. Thus far, a relatively low level of R&D expenditures is a typical characteristic of CEE countries. The ratio of patents in CEE countries is extremely low. The activities of multinational enterprises explain the smaller gap in the presence of high technologies compared with the other European economies. In terms of education there are no clear patterns for CEE countries. Some states show similarities with Continental education systems. Slovenia was the only one to fall into the group of – mainly Nordic – countries with the most successful educational system.
Keywords: O3; 330; knowledge; innovation